Laboratory Studies to Increase Oil Production Using Methyl Ester Sulfonate Injection on X Field - Aditya Rachman; Rini Setiati; Kartika Fajarwati Hartono (Journal of Earth Energy Science, Engineering, and Technology, 2019)
The majority of petroleum production comes from the brown field where production has decreased from year to year in Indonesia. To increase the recovery factor of petroleum from the reservoir, an advanced step of production is required, Enhanced Oil Recovery (EOR), which can optimize the depletion of old oil fields. EOR is the application of technology that requires cost, technology and high risk. Therefore, before implementing EOR, in a field, we must carefully evaluate both technically and economically to obtain an optimal additional recovery. This research was conducted to increase oil production by injection of Methyl Ester Sulfonate (MES). This study begins with a screening parameter crude oil, formation water, Berea’s core, and determination of phase behavior, interfacial tension (IFT), thermal stability, imbibition, and core flooding tests. The result for concentratin optimum in 0.3% MES and had IFT 0.3267 dyne/cm. The results of core flooding tests are: Recovery factor of waterflooding is 33.95 % and recovery factor of MES injection is 4.19 %.